Thermal and physicochemical properties of red tilapia (Oreochromis niloticus) surimi gel as affected by microbial transglutaminase - Seighalani, Fariba Zad Bagher; Bakar, Jamilah; Saari, Nazamid; Khoddami, Ali (CSIRO Publishing, 2017)
Thermal and physicochemical properties of red tilapia (Oreochromis niloticus) surimi gel incorporated with different levels of microbial transglutaminase (MTGase) were investigated. Surimi samples mixed with various concentrations of MTGase were subjected to two-stages heating (at 45 C followed by 90 C) to prepare surimi gel. Samples formulated with 0.30 MTGase (units/g surimi) showed the highest breaking force and deformation, and lowest expressible water content among treatments. Highest storage modulus was found in the gels mixed with 0.30 MTGase (units/g surimi). Compared with control surimi gel, addition of microbial transglutaminase to levels 0.10, 0.20 and 0.30 (units/g surimi) increased the enthalpy and maximum transition temperature of myosin. Results suggest that up to 0.30 MTGase (units/g surimi) could improve texture, colour, water-holding capacity, elasticity and thermal stability of red tilapia surimi gel.